INTERVENSI MIKRO PEKERJA SOSIAL TERHADAP KLIEN DI BALAI REHABILITASI SOSIAL PENYANDANG DISABILITAS FISIK (BRSPDF) WIRAJAYA KOTA MAKASSAR - Andi Amirah Humairah Yakub; Muhammad Iqbal Latief; Hasbi Hasbi (Department of Sociology Faculty of Social and Political Sciences, 2021)
This study aims to find out the form of empowerment and social exchange effects of micro-interventions in Balai Rehabilitasi Sosial Penyandang Disabilitas Fisik (BRSPDF) Wirajaya Makassar City. This research was conducted out for 3 months and was conducted from February 2021 to April 2021 in Balai Rehabilitasi Sosial Penyandang Disabilitas Fisik (BRSPDF) Wirajaya Makassar City. This research uses descriptive qualitative research based on case study research with 6 subjects consisting of social workers and clients of BRSPDF Makassar City. Based on the research results, it was found that the in the micro intervention process, there are seven stages of intervention namely engagement, intake and contract, assessment, planning, intervention, evaluation and termination. The form of intervention empowerment carried out in accordance with the stages did not find any problems. Social workers at BRSPDF Wirajaya Makassar City carry out all stages of micro intervention on interventions that are applied to people with physical disabilities in community life readiness guidance programs, such as sewing skills, automotive, electronics, etc. The intervention process produces people with physical disabilities who have stronger mental and skills to be equipped to live independently in the community, such as opening a convection business, service center, printing house, etc. BRSPDF Wirajaya also cooperates with big companies to provide opportunities for people with disabilities such as alfamart or alfamidi, which every year the hall will send 10-20 clients. Keywords: Micro Intervention, Social Worker, Persons with Physical Disabilities